La política externa brasileña y la crisis en el Atlántico Sur : una evaluación - Lafer, Celso (Estudios Internacionales, 1982)
In this paper, an evaluation of the position and behavior of Brazilian diplomacy in the recent South Atlantic crisis, which meant the war between Argentina and Great Britain, is carried out. We argue that during the Malvinas crisis, Brazil succeeded in helping to "circumscribe the negative effects of the conflict" and now has the task of helping to circumscribe the negative effects of "a mechanical solution." In the specific case of the Malvinas, this means, at the bilateral and multilateral level, the reiteration of the Brazilian position both in relation to Argentine rights in the field of the great world colonization process and the need for a negotiated solution to the problem as a means of overcoming the current instability.